The Feasibilty of Student Worksheets with STEM Approach to Understanding of Earthquake Disaster Mitigation - Kosim Kosim; Riri Deansikutari; Muh. Mahkrus; Gunawan Gunawan; Hikmawati Hikmawati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to feasibility of student worksheets with a STEM approach in earthquake disaster mitigation The STEM approach is an approach that combines four aspects of science, namely science, technology, engineering and mathematics. The research method used is Research and Development (R&D) with the ADDIE model consisting of four stages, namely Analysis, Design, Development, Implementation, and Evaluations. The research phase is limited to the stage of development. The product developed is the Student Worksheet. The feasibility of the student worksheets developed was seen from the results of the validation. by three experts who calculated the validity and reliability of the student worksheets. The response questionnaire was distributed to 30 students of the Physics Departement in FKIP - University of Mataram. The results show that the validity of student worksheets was included in the very valid category and it was reliable criteria. The results of student responses showed a very good response (98.33%). Beside that the implementing of student worksheets to 30 students show good assessment (93.33%). Thus, it can be concluded that the student worksheets that have been developed with the STEM approach can improve the understanding students to the earthquake disaster mitigation